Communists and Auto Workers: The Struggle for Industrial Unionism in the Canadian Automobile Industry, 1925-36 - Manley, John (Labour / Le Travail, 1986)
During the 1920s and early 1930s the struggle for industrial unionism in the Canadian auto industry was predominantly organized and led by Communist Party members. They, however, had little success with workers whose enjoyment of unusually high industrial wages was tempered by the knowledge that they themselves were almost as replaceable and interchangeable as the parts they assembled. An upswing of industrial militancy in the 1928-9 boom suggested that "Fordism" was not immutable, but any possibility of establishing a "red" auto union disappeared with the arrival of the Depression. Nevertheless, during the grimmest crisis years, Communists kept the idea of industrial unionism alive, and in semi-clandestine conditions built a network of union activists. The formation of the CIO and UAW gave this group the opportunity to turn their aspirations into reality.
Keywords: ACTIVISTS; AUTOMOBILE industry; Canada; Communist Party of Canada; FINANCIAL crises; FORDISM; LABOUR/LE Travail (Book); Labor Unions; PERSONNEL management; Wages

Communism and the Canadian Working Class During the Great Depression: The Workers' Unity League, 1930-1936 - Manley, John (Dalhousie University, 1984)
The Communist Party of Canada's (CPC) attempts to operate the United Front tactics laid down by Lenin and the Comintern in 1920-22 foundered on the CPC's failure to come to terms with the profound character of labour's post-war defeat or with its own marginality. The task of creating a mass party capable of leading, in the not-too-distant future, a revolutionary struggle for power encouraged the CPC to ignore the laborious and modest process of building support around small workplace issues and to prefer working through a spurious united front organization, the Trade Union Educational League, which was little more than a mouthpiece for a succession of abstract propaganda campaigns. When none of these propelled the party to mass status, but rather drove a wedge between it and the Trades and Labour Congress, the ground was prepared for acceptance of the diametrically opposite tactics of the "Third Period", which with much justice have been criticised for their political stupidity. The tardiness with which the CPC applied them underlined the fact that, however much the leaders of the labour movement might have "betrayed" the rank and file, it was hard to see them as "social fascists" who had to be combatted with even more vigour than that usually reserved for the bosses. From the beginning, when they terminated an interesting alliance between the CPC and national unionism, to the end, when they retarded the CPC's recognition of the possibilities opened up by the emergence of the CIO, these tactics had negative consequences. Yet they also helped bring limited political gains for the CPC, which entered the latter half of the 1930s stronger than it had ever been, and organizational advances for the Canadian working class, in the shape of at least the first few bricks in the foundations of mass industrial unionism. In addition, the complementary unemployed movement mobilized tens of thousands of workers and their families against the asperities of the depression. By 1936, the CPC had undeniably "carved out" for itself, a decent niche in the labour movement.
Keywords: Education